The Moral Implications of Human and Animal Vulnerability - Martin, Angela K. (Springer Nature, 2023)
In this open access book, Angela K. Martin thoroughly addresses what human and animal vulnerability are, how and why they matter from a moral point of view, and how they compare to each other. By first defining universal and situational human vulnerability, Martin lays the groundwork for investigating whether sentient nonhuman animals can also qualify as vulnerable beings. She then takes a closer look at three different contexts of animal vulnerability: animals used as a source of food, animals used in research, and the fate of wild animals.